Penyelesaian Kerugian pada Pendapatan Negara melalui Pengungkapan Ketidakbenaran (Suatu Kajian Hukum Doktrinal dalam Sistem Perpajakan) - Arifki, Nindi Achid (Universitas Negeri Surabaya, 2019)
Losses on state revenues are clauses that are explicitly stated in general provisions and taxation procedures. at the praxis level, arrangements relating to the content and limitation of loss clauses on state revenues cannot be found and expressly stated in the construction of tax law or in the realm of state financial law construction. Using the method of doctrinal legal research and by utilizing secondary data and the hermeneutic approach, this paper aims to examine the discourse of settlement of losses in state revenues through disclosure of untruthfulness in juridical construction of state financial law and regulations in the field of taxation. The conclusion obtained is that there are no strict norms that regulate the content and limits of loss clauses on state revenues, so that the discourse of settlement of losses on state revenues through disclosure of untruth can be legitimate and possible.